Time trends and persistence of the return difference between growth and value investment strategies - Manuel Monge; Rafael Hurtado; Juan Infante (PLoS ONE, 2025)
This paper examines the dynamic disequilibrium between value investing and growth strategies, focusing on the structural changes induced by the COVID-19 pandemic. Using fractional integration and Markov-switching dynamic regression (MS-DR) models, we analyze persistence and regime shifts. The results reveal that, prior to March 2020, the return difference was in a regime of high persistence and no reversion to the mean, making the deviations long-lasting. After the pandemic, the system shifted to a regime of moderate persistence with reversion to the mean, indicating that the return differences now tend to correct over time. This regime shift, confirmed by the Markov switching model, highlights a permanent change in the dynamics of value and growth strategies, which significantly affects their long-term equilibrium.